Development and characterization of Petit suisse added green banana biomass with passion fruit cover (Research, Society and Development, 2021)
This work aimed to develop Petit suisse cheese with the addition of green banana biomass. Skimmed milk added sucrose was used to prepare the dough, followed by heat treatment at 83°C for 30 minutes, cooling to 39°C and adding cultures of the bacteria Lactobacillus delbruechii subsp. bulgaricus and Streptococos salivarius subsp. Thermophilus and coagulant. The mixture was incubated at 39°C and remained until it reached 35 °Dornic acidity and pH 5.5, and was then kept refrigerated for 15 hours at 5°C and the addition of green banana biomass (10%). Passion syrup with seeds was added for topping. Analyzes of moisture, protein, total fat, ash, carbohydrates, calcium, sodium, acidity and texture parameters were performed. Sensory acceptance and purchase intention tests were also carried out. According to physical and chemical analyzes, it was found that the product met the standards of the Petit Suisse cheese legislation. The product had a content of 0.0% of fats and high averages of sensory acceptance, with the majority of the tasters responding that they “liked it a lot”. And when it comes to purchasing intent research, most tasters would "probably buy" the cheese. In this way, it was concluded that Petit cheese suisse "zero fat" with the addition of green banana biomass and passion fruit syrup topping presents a high market potential and may be another alternative for healthy eating.